Delayed admissions and efficacy of steroid use in patients with critical and severe COVID-19: an apprehensive approach. (27th September 2021) - Akhtar, Hashaam; Khalid, Sundas; Rahman, Fazal-ur-; Ali, Sabahat; Afridi, Maham; Khader, Yousef S; Hassan, Faheem; Akhtar, Nasim; Khan, Muhammad Mujeeb; Ikram, Aamer
Abstract: Background: Inadvertent delays in access to appropriate therapeutic interventions in high-risk group coronavirus disease 2019 (COVID-19) patients contribute to mortality in patients with severe/critical disease presentation. Objectives: The aim of this study was to determine the effect of timely admission to the hospital on mortality of patients with severe/critical COVID-19. Another secondary aspect of this study was to observe the efficacy of time-dependent use of corticosteroids on mortality of critical/severe COVID-19 patients. Methods: Clinical data of 659 patients with severe/critical COVID-19, admitted to four major tertiary care hospitals from the Islamabad-Rawalpindi region of Pakistan was retrospectively collected from a period February–August 2020. Multivariate logistic regression analysis was carried out to determine the predictors of mortality in severe/critical COVID-19 patients. Results: Out of a total of 659 patients, 469 (71.2%) patients died. Age > 60 years, presence of hypertension, heart disease and kidney disease along with late admission (>5 days) were significant predictors of mortality in patients with severe/critical COVID-19. Conclusions: The study highlights the importance of well-timed provision of appropriate medical interventions control COVID-19-associated mortality.